Regional seminar on the search for identity in architecture : [Working papers] - Regional Seminar on The Search for Identity in Architecture (1983 : Universiti Teknologi Malaysia); Universiti Teknologi Malaysia (Kuala Lumpur : Universiti Teknologi Malaysia, 1983)
South East Asian architectural traditions : an approach to the search for identity/ Dr. Khoo Joo Ee -- Identity in diversity within unity/ Robi Sularto Sastrowardoyo -- Cultural identity in architecture as perceived from a Singapore view point/ Tay Kheng Sook -- The Indian experience and the search for some light at the other end/ Romi Khosla